KEWENANGAN PENGADILAN NEGERI MEMUTUS SENGKETA ANTARA PARTAI POLITIK DAN KOMISI PEMILIHAN UMUM - Mahmudi, Mohammad (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
The District Court is a general court institution that handles criminal and civil cases which is domiciled at the district or city level, while a state institution is a body that has the authority and duties for certain matters and is specific in nature, such as the KPU which functions as an organizer of general elections that cannot be separated from conflicts or disputes in the stages of holding elections, in this case there are issues that cause dynamics, namely the result of a lawsuit filed by the just and prosperous people's party in suing the KPU because the Prima party did not pass as a political party candidate for the 2024 election. This type of research is normative research. (legal research), namely placing law into a system of norms. This research uses a statutory approach (statute approach) and an analytical approach (analitycal approach). The authority of the district court in deciding disputes over the general election process that occurred as a result of the failure of political parties participating in the election with the KPU is beyond the competence of the general court and claims cannot be accepted. The election law regulates three matters relating to election dispute resolution: first, settlement Election process disputes are conducted through the election supervisory body (Bawaslu). Second, the settlement of election disputes is carried out by legal means through the State Administrative Court (PTUN) because every decision issued by the KPU is a State Administrative decision. Third, the settlement of disputes over the results of general elections is carried out through the Constitutional Court as regulated by the 1945 Constitution.